Fiscal multipliers and foreign holdings of public debt - Fernando Broner; Daragh Clancy; Aitor Erce; Alberto Martin (European Central Bank (ECB), 2019)
This paper explores a natural connection between fiscal multipliers and foreign holdings of public debt. Although fiscal expansions can raise domestic economic activity through various channels, they can also have crowding-out effects if the resources used to acquire public debt reduce domestic consumption and investment. These crowding-out effects are likely to be weaker when governments have access to foreign markets to place their debt, increasing the size of multipliers. We test this hypothesis on (i) post-war US data and (ii) data for a panel of 17 advanced economies from the 1980's to the present. To do so, we assemble a novel database of public debt holdings by domestic and foreign creditors for a large set of advanced economies. We combine this data with standard measures of fiscal policy shocks and show that, indeed, the size of fiscal multipliers is increasing in the share of public debt held by foreigners. In particular, the fiscal multiplier is smaller than one when the foreign share is low, such as in the U.S. in the 1950's and 1960's and Japan today, and larger than one when the foreign share is high, such as in the U.S. and Ireland today.
Keywords: E62; F32; F34; F36; F41; F62; F65; G15; H63; 330; sovereign debt; fiscal multiplier; foreign holdings of public debt